Development and validation of the career decision making indicator (CDMI) using exploratory and confirmatory factor analysis / Muna Saif Abdullah Al-Kalbani - Abdullah Al-Kalbani, Muna Saif (2010)
Using data from 1880z high school students, a series of five studies developed and validated a measure of the career decision-making tailored to adolescents, the Career Decision Making Indicator (CDMI). The CDMI measure the individual along eight dimensions: Decidedness, Comfort, Career Choice Anxiety, External Barrier, Need for Information, Readiness, Career Salience, and Inconsistent Information. The instrument has been validated through a scientific method to ensure its reliability and validity. Two advanced statistical methods were used, namely: Exploratory factor analysis (EFA) and Confirmatory factors analysis (CFA). EFA was used to identify the underlying dimensions of each construct of the instrument. CFA is used to confirm the dimensions and to analyse the fitness of the data collected in the hypothesized model. The results provide evidence that the developed instrument achieved sound psychometric properties. The overall reliability value of Cronbach’s Alpha was .935. The result of EFA showed that, the CDMI constructs produced eight significant factors. The CFA results showed that the goodness-of-fit indices for the model were as follows: χ2=1674.711, df= 674, CMIN/df= 2.485, CFI=.917, GFI= .930, AGFI= .919, PCOLOSE =1.00 and RMSEA =.036; each of the indices was above the threshold values. Results are discussed in terms of implications for future research and career development efforts.